2020
DOI: 10.1186/s40360-020-0396-5
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin-ceftazidime administration regimens combat Pseudomonas aeruginosa in the hollow-fiber infection model simulating abnormal renal function in critically ill patients

Abstract: Background: The purpose of this study was to investigate the bactericidal effects of levofloxacin and ceftazidime as both monotherapy and combination therapy, and to determine their effects on resistance suppression in patients with normal and abnormal (Ccr:16-20 mL/min) renal function. Common clinical administration regimens to provide reference values were further evaluated. Methods: The 7-d hollow-fiber infection model was used to inject the Pseudomonas aeruginosa standard strain (ATCC27853), which simulate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…A compartment model is added to the system to simulate the in vitro experiment of different half-life drugs [ 15 ]. Based on the apparent volume of distribution (V), when the drug distribution in the body reaches dynamic equilibrium and the volume of the model, the dosage can be calculated [ 16 ]. HFIM is used to study Mycobacterium tuberculosis , for which the EMA issued a qualification opinion.…”
Section: Construction and Application Of Hollow Fiber Infection Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A compartment model is added to the system to simulate the in vitro experiment of different half-life drugs [ 15 ]. Based on the apparent volume of distribution (V), when the drug distribution in the body reaches dynamic equilibrium and the volume of the model, the dosage can be calculated [ 16 ]. HFIM is used to study Mycobacterium tuberculosis , for which the EMA issued a qualification opinion.…”
Section: Construction and Application Of Hollow Fiber Infection Modelmentioning
confidence: 99%
“…It can also be combined with the mechanism model to predict the effect of different administration schemes [ 56 ]. In the study of the bactericidal effect of levofloxacin and ceftazidime on P. aeruginosa , it was also found that the inhibitory effect of the combination regimen on drug resistance in patients with normal renal function and renal insufficiency was different, and nodes of drug resistance could also be observed in the in vitro model [ 16 ].…”
Section: Construction and Application Of Hollow Fiber Infection Modelmentioning
confidence: 99%
“…More recently, the hollow-fiber infection model (HFIM), which has been widely used to explore how to rationally use antibiotics and reduce bacterial resistance, can provide valuable information about the interactions between antibiotics, bacteria, and host ( Nielsen and Friberg, 2013 ; Burgos and Rodvold, 2019 ; Zhao et al, 2020 ; Agyeman et al, 2021 ). In the HFIM, Tsuji et al (2012) found that the front-loaded dose of linezolid against VREfm could provided the maximal bacterial reductions of about 3 log 10 CFU/ml, but the front-loaded regimens did not inhibit the expansion of resistant subpopulations against VREfm with resistant alleles.…”
Section: Introductionmentioning
confidence: 99%
“…With a more sophisticated experimental setup, the dynamic model can be further modified to mimic two antibiotic exposures simultaneously, where the elimination half-lives of the individual antibiotics are distinctively different [4]. This framework has been the "gold standard" of the field for more than three decades, and has been used by multiple investigator groups to evaluate combination therapy [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%